Private Paris : Private #10 - Patterson, James, 1947-; Sullivan, Mark T.; Snyder, Jay (New York : Hachette Audio, 2016)
While visiting Private's Paris office, Jack Morgan finds himself in pursuit of a client's granddaughter, who is on the run from a drug dealer and investigating the deaths of several of France's cultural elite.
Read by Jay Snyder.
Keywords: Private investigators -- Fiction; Paris (France) -- Fiction; Suspense fiction; Audiobooks